Patterns of Observed Child Participation and Proximity to a Small Group with Teacher in Swedish Preschool Free Play - Åström, Frida (Jönköping University, 2022)
Swedish preschool is a preschool for all children and free play is an important educational activity. The question is whether all children are participating (ie, are attending important activities and are engaged when they are there) to a sufficient extent in preschool free play? This study aims to explore children's observed participation based on quantitative observational data and a person-oriented method of analysis. A series of systematic instantaneous observations á 3 seconds (M = 19.50, SD = 8.40) of individual children (n = 453) with a minimum age of 36 months, were carried out continuously for 1-2 full days in 56 preschool units in southeast Sweden. Only observations where the overall activity (activity setting) was free play (indoors and outdoors) were used in the analysis. The summed observations resulted in frequency data for four types of activities; pretend play, associative / cooperative interactions, proximity to a small group incl. teachers, and level of engagement (level of focus or effort in the activity) and were selected as important based on the Swedish preschool context and previous research. Proportions (divided by the individual's total number of observations in free play) of the individual activities were calculated. The four proportion variables were used in a series of cluster analyzes to find distinct and interpretable clusters or patterns of participation where the children in a cluster were highly similar in all variables, and at the same time were very different from children in the other clusters. The clusters were then compared based on child characteristics (age, gender, need for special support, receiving mother tongue support) answered by preschool staff, and preschool unit characteristics (number of children, number of staff, children / staff ratio, number of children with mother tongue support, number of children in need of special support, number resource staff) answered by the preschool director / principal, to see if certain characteristics were more common in some clusters than in others.

The results identified eight distinct and interpretable patterns that could be arranged from higher to lower participation. Most interesting were two clusters of children that indicated low to very low observed participation, and with high and low proximity to a small group of teachers, respectively. The children in the cluster with a very low participation pattern and low proximity to a small group of teachers were more often children with another mother tongue, and more children came from units with more resource staff. It is noteworthy that few of these children were considered to need special support according to the preschool staff. The children also came from different preschool units. Children in the cluster with a low participation pattern and high proximity to a small group of teachers more often came from preschool units where more children had a different mother tongue. No significant difference between the clusters was noted in the number of children in need of special support, although trends could be discerned.

Data was collected with systematic observations with the help of manual-based instrument Child Observation in Preschool (COP), adapted to the Swedish preschool context. The observations consists of many snapshots of individual children across a preschool day, at least. Several aspects of the child's current activity are coded. Individual data is summed across the observations, and proportions of different activities (pretend play, associative/cooperative interactions, proximity to small group with teacher, level of engagement) were calculated. Frequency and proportionate data from the observations are available in the data set, as well as child and preschool unit background information.

Svensk förskola är en förskola för alla barn och fri lek är en viktig pedagogisk aktivitet. Frågan är om alla barn är delaktiga (dvs, befinner sig i viktiga aktiviteter och är engagerade när dom är där) i tillräcklig omfattning i förskolans fria lek? Denna studie ämnar utforska barns observerade delaktighet utifrån kvantitativa observationsdata och ett person-orienterat analyssätt. Flera systematiska ögonblicksobservationer á 3 sekunder (M = 19.50, SD = 8.40) av enskilda barn (n = 453) med en minimålder om 36 månader, genomfördes kontinuerligt under 1-2 heldagar på 56 förskoleavdelningar i sydöstra Sverige. Enbart observationer där den överordnade aktiviteten (activity setting) var fri lek (inne samt ute) användes i analysen. De summerade observationerna resulterade i frekvensdata för fyra typer av aktiviteter; låtsaslek, associativ/kooperativ lek, närhet till liten grupp inkl. lärare, samt nivå av engagemang (nivå av fokus eller ansträngning i aktiviteten) och valdes ut som viktiga utifrån svensk förskolekontext och tidigare forskning. Proportioner (dividerat på individens totala antal observationer i fri lek) av de enskilda aktiviteterna räknades ut. De fyra proportionsvariablerna användes i en serie av klusteranalyser för att hitta distinkta och tolkningsbara kluster eller mönster av delaktighet där barnen i ett kluster i hög grad liknade varandra i samtliga variabler, och samtidigt var olika från barn i övriga kluster. Klustren jämfördes sedan baserat barn karaktäristika (ålder, kön, behov av särskilt stöd, erhåller modersmålsstöd) besvarade av förskolepersonal, och förskoleavdelningskaraktäristika (antal barn, antal personal, barn/personal ratio, antal barn med modersmålsstöd, antal barn i behov av särskilt stöd, antal resurspersonal) besvarade av förskolechef/rektor, för att se om vissa karaktäristika var vanligare hos vissa kluster än hos andra.

Resultaten identifierade åtta distinkta och tolkningsbara mönster som kunde ordnas från högre till lägre delaktighet. Mest intressant var två kluster av barn som indikerade låg till mycket låg observerad delaktighet, och med hög respektive låg närhet till liten grupp med lärare. Barnen i klustret med mycket lågt delaktighetsmönster och låg närhet till liten grupp med lärare var oftare barn med annat modersmål, och fler barn kom från avdelnignar med fler resurspersonal. Noterbart är att få av dessa barn ansågs behöva särskilt stöd av förskolepersonalen. Barnen kom också från olika förskoleavdelningar. Barn i klustret med lågt delaktighetsmönster och hög närhet till liten grupp med lärare kom oftare från förskoleavdelningar där fler barn hade ett annant modersmål. Ingen signifikant skillnad mellan klustren noterades i antalet barn i behov av särskilt stöd, även om tendenser kunde urskiljas.

Data har samlats in med hjälp av systematiska observationer genom det manualbaserade instrumentet Child Observation in Preschool (COP) som anpassats till svensk förskolekontext. Observationerna innebär att flera ögonblicksbilder av individuella barn görs under minst en heldag i förskolan. Flera aspekter av individens aktuella aktivitetet kodas. Därefter har data summerats på individnivå och proportionerlig fördelning av aktiviteter (dividerat med individens totala antal observationer i fri lek) har kalkylerats. Frekvensdata och proportionsdata för barn återfinns i dataseten samt bakgrundsinformation om barn och avdelningar.
Mönster i barns observerade delaktighet och närhet till liten grupp med lärare i den svenska förskolans fria lek
Keywords: preschool children; förskolebarn; pre-primary schools; förskolor; observation (data collection); observation (datainsamling); activity; aktivitet; language; språk; involvement; engagemang; inclusion; inkludering; free play; fri lek; cluster; kluster; participation; delaktighet; mother tongue; modersmål; special support; särskilt stöd; person-oriented; person-orienterad; EDUCATION; UTBILDNING; Compulsory and pre-school education; Obligatorisk utbildning och förskoleutbildning; General health and well-being; Allmän hälsa och välbefinnande; Children; Barn; PSYCHOLOGY; PSYKOLOGI; Social Sciences; Samhällsvetenskap; Psychology; Psykologi; Educational Sciences; Utbildningsvetenskap